Transforming Sunday school education: A study on goal setting, program planning, implementation and evaluation in Bebelan’s Pentecostal church - Iskandar, Ferdinand; Tambunan, Daulat Marulitua (UIN Raden Mas Said Surakarta, 2024)
This research examines the implementation of Sunday School education at the Pentecostal Church of Indonesia in Babelan, a rapidly developing district in Bekasi Regency, West Java, Indonesia. Babelan is a suburban area that reflects both urban growth and traditional community values, making it an essential context for studying the role of religious education in shaping children's spiritual development. The primary objective of this study is to evaluate the aspects of goal setting, program planning, implementation, and evaluation of goal achievement in Sunday School education. A qualitative approach was employed, using observation, interviews, and document analysis for data collection. The findings reveal that the process of determining Sunday School goals lacks clarity, program planning does not sufficiently align with the developmental needs of children, and program implementation is influenced by the qualifications and commitment of the teachers. Furthermore, the evaluation of goal achievement is not optimally performed. The study concludes that improvements are needed in all areas of Sunday School education, particularly in setting clear objectives, aligning programs with children's needs, enhancing teaching quality, and implementing structured evaluations to improve the effectiveness of children's religious education in Babelan's dynamic community context.